2022
DOI: 10.1177/10963480221137779
|View full text |Cite
|
Sign up to set email alerts
|

Instant Karma: How the Karmic-Investment Mindset Affects Customer Engagement With Corporate Charitable Giving Requests

Abstract: Corporate charitable giving (CCG) is increasingly pervasive in the global hospitality industry. Among various subtypes of CCGs, many hospitality companies request donations from customers during the service delivery or payment process to encourage customer engagement and co-created social responsibility. Karma—the implicit belief that the universe rewards good deeds and punishes wrongdoings—resonates with consumers’ prosocial behaviors, yet little is known about how karma beliefs, along with various donation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 104 publications
(156 reference statements)
0
1
0
Order By: Relevance
“…The study revealed that green innovation enhances the sustainability of pilgrimage destinations and improves tourist satisfaction, emphasizing the potential benefits of integrating sustainability practices in religious tourism. Xue and Mattila (2022) examined the influence of the karmic-investment mindset on customer engagement with corporate charitable giving requests. The authors found that the karmic-investment mindset positively affects customer engagement, highlighting the potential of incorporating ethical and philanthropic initiatives in business strategies.…”
mentioning
confidence: 99%
“…The study revealed that green innovation enhances the sustainability of pilgrimage destinations and improves tourist satisfaction, emphasizing the potential benefits of integrating sustainability practices in religious tourism. Xue and Mattila (2022) examined the influence of the karmic-investment mindset on customer engagement with corporate charitable giving requests. The authors found that the karmic-investment mindset positively affects customer engagement, highlighting the potential of incorporating ethical and philanthropic initiatives in business strategies.…”
mentioning
confidence: 99%